Resting energy expenditure in adult patients with Crohn's disease. Issue 2 (April 2017) - Sammarco, Rosa; Marra, Maurizio; Pagano, Maria Carmen; Alfonsi, Lucia; Santarpia, Lidia; Cioffi, Iolanda; Contaldo, Franco; Pasanisi, Fabrizio
Summary: Background & aims: Crohn's disease (CD) is a chronic intestinal disorder of unknown etiology involving any section of the gastrointestinal tract often associated with protein-energy malnutrition (PEM). Increased resting energy expenditure (REE) unmatched by adequate dietary intake is amongst the pathogenetic mechanisms proposed for PEM. Aim of this study was to evaluate REE in CD patients receiving or not immuno-suppressive therapy as compared to controls. Methods: 36 CD patients (22 M and 14 F, age range 18–55 years) clinically stable and without complications since at least 6 month were studied. REE was evaluated by indirect calorimetry and body composition by BIA. Full biochemistry was performed. Patients were divided into two groups: Group 1 (G1 = 12 patients) without and Group 2 (G2 = 24 patients) with immuno-suppressive therapy. Results: The two groups were similar for age, height and BMI whereas significantly differed for weight (G1 vs G2: 56.9 ± 7.44 vs 62.3 ± 8.34 kg), fat free mass (FFM: 40.4 ± 5.73 vs 48.2 ± 7.06 kg), fat mass (FM: 17.0 ± 3.55 vs 13.9 ± 5.54 kg) and phase angle (PA: 5.6 ± 1.4 vs 6.5 ± 1.0°). Serum inflammation parameters were significantly higher in G1 than in G2: hs-PCR: 7.76 ± 14.2 vs 7.16 ± 13.4 mg/dl; alfa 2-protein: 11.7 ± 3.69 vs 9.74 ± 2.08 mg/dl; fibrinogen: 424 ± 174 vs 334 ± 118 mg/dl (p < 0.05). REE was higher in G2 vs G1: 1383 ± 267 vs 1582 ± 253 kcal/die (p < 0.05) both in men: 1579 ± 314 vs 1640 ± 203 and women: 1267 ± 140 vs 1380 ± 132. Nevertheless, when corrected for FFM, REE resulted higher in G1 than G2 (34.8 ± 4.89 vs 33.0 ± 4.35 kcal/kg, p < 0.05) group, also higher compared to our, age and sex matched, control population (REE/FFM: 30.9 ± 4.5 kcal/kg). Conclusions: Our preliminary results show that REE when adjusted for FFM is increased in clinically stable CD patients and mildly reduced by immunosuppressive therapy possibly through a direct action on inflammation and on body composition characteristics.